THE ROLE AND IMPORTANCE OF ICT IN THE DEVELOPMENT OF THE TAX SYSTEM - Oymatova G.M. (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
In this article, it is described the actual problems of using information and communication technologies in improving tax administration, discussed the factors that cause them, and made suggestions to eliminate these problems.